The Role of Drug Swallowing Supervisors (PMO) in the Success of Pulmonary Tuberculosis Treatment in the Work Area of ​​Community Health Center X - Rahmad Gurusinga (JURNAL KESMAS DAN GIZI (JKG), 2026)
Tuberculosis (TB) is an infectious disease that remains a global health problem, with treatment success heavily influenced by patient compliance in taking medication. One effort to improve compliance is through the role of Drug Supervisors (PMOs). This study aims to determine the relationship between the role of PMOs and the success of TB treatment. This study used an analytical design with a cross-sectional approach. The sample size was 43 respondents who were TB patients. Data were collected using observation sheets and analyzed using the chi-square test. The results showed that most respondents with a good PMO role had a treatment success rate of 88.0%, while those with a sufficient PMO role had a treatment success rate of 50.0% and those with a poor PMO role had a treatment success rate of 33.3%. Overall, the treatment success rate reached 69.8%. The statistical test results showed a p-value of 0.007 (p < 0.05), indicating a significant relationship between the role of PMOs and the success of TB treatment. The conclusion of this study is that the role of PMOs is significantly related to the success of TB treatment. Therefore, improving the quality of the PMO role is essential to support patient compliance and improve the success of TB therapy.